The institutional context of financialization - Ząbkowicz, Anna (Publishing House of the Wrocław University of Economics, 2009)
The phenomenon of financialization of non-financial corporations has been widely observed in the US economy since the 1980s and since the 1990s in some European economies as well. This is as a pattern of accumulation in which profits accrue primarily through financial channels rather than through trade and commodity production [Krippner 2005, p. 181]. “Financial” here refers to activities relating to the provision (or transfer) of liquid capital in expectation of future interest, dividends, or capital gains. There is a range of research that points to the increasing salience of finance in the economy [Brenner 2002; Epstein (ed.) 2005]. The literature addressing the problem with reference to firms tends to focus either on organizational developments with strong link to shareholder view in corporate governance [Lazonick, O’Sullivan 2000; Williams 2000], or on activities inside financial markets [Phillips 2002]. This paper deals with the financialization from the perspective of institutional economics. This means an approach broader than a mere “technical” analysis of corporate balance sheets, which aims to identify relation between such corporate behaviour and the nature of contemporary economy, described by a range of social science research since the 1980s. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 475-483